1994
DOI: 10.1029/94gl00178
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the performance of the ice and ocean tracking modes of the ERS‐1 radar altimeter over non‐ocean surfaces

Abstract: The European Space Agency's ERS‐1 radar altimeter is the first to include separate operating modes to optimise performance over both ocean and non‐ocean surfaces. As part of the ERS‐1 commissioning activities, we have carried out a study of the tracking performance of this instrument over non‐ocean surfaces. Statistics for land ice, sea ice, arid lands, and inland water are presented. Performance in both operating modes is shown to be better than that of previous missions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…The altimeter (1991 to present) possesses an ice-tracking mode facility which has enabled increased tracking performance over land [Scott et al, 1994]. The enviromnental satellite mission (ENVISAT, launch in approximately 1999) will also carry a modified radar alti•neter (known as RA 2) which will have "guar,-mteed continuity" performance, i.e., operation without the loss of surface lock, over nonocean surfaces [Resti, 1993].…”
Section: Altimeter Tracking Performancementioning
confidence: 99%
“…The altimeter (1991 to present) possesses an ice-tracking mode facility which has enabled increased tracking performance over land [Scott et al, 1994]. The enviromnental satellite mission (ENVISAT, launch in approximately 1999) will also carry a modified radar alti•neter (known as RA 2) which will have "guar,-mteed continuity" performance, i.e., operation without the loss of surface lock, over nonocean surfaces [Resti, 1993].…”
Section: Altimeter Tracking Performancementioning
confidence: 99%
“…Through a repeat cycle of 165 days, the ground track spacing at 79øS is 2 km, providing a high density of height measurements across the plateau. Through the application of corrections to the height estimate [Cudlip et al, 1994] and the best available orbit ephemeris [Scharroo et al, 1993], an individual height measurement over the plateau has a precision of 25 cm and an accuracy of about 1 m [Scott et al, 1994]. Two cycles of data, offset from each other by half the track separation, from the 165-day repeat mission (comprising 250,000 individual measurements) were averaged and interpolated across a 3-km grid to provide the data from which the detailed surface elevation map of the ice sheet above the radio-echo lines of Lake Vostok was made (Figure 1).…”
Section: Satellite Radar Altimetrymentioning
confidence: 99%
“…Initial studies showed that during the ERS 1 ice mode operating periods, 64% of wetland/river surfaces were acquired [Scott et al, 1994]. Although both instruments are set in an orbit with a longer repeat period (35 days), their greater coverage of rivers/wetlands (theoretically, 3 times that of TOPEX/POSEIDON), with an along-track spacing of -330 m, offers the potential for more regions to be studied and the minimum river width limit to be narrowed.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%